Evidence of short-term belowground transfer of nitrogen from Acacia mangium to Eucalyptus grandis trees in a tropical planted forest - Paula, Ranieri Ribeiro; Bouillet, Jean-Pierre; Ocheuze Trivelin, Paulo César; Zeller, Bernd; Leonardo de Moraes Gonçalves, José; Nouvellon, Yann; Bouvet, Jean-Marc; Plassard, Claude; Laclau, Jean-Paul [UNESP] (Elsevier, 2015)
The short-term belowground transfer of nitrogen from nitrogen-fixing trees to companion trees has never been studied in the field. A 15N pulse-labeling study was conducted in a mixed plantation of Acacia mangium and Eucalyptus grandis at the peak of leaf area, 26 months after planting. 15N-NO3 - was injected into the stem of one big Acacia tree in three plots. 15N was traced over 2 months in the labeled Acacia tree as well as in neighboring Eucalyptus trees. For both species, young leaves were sampled, as well as fine roots and the rhizosphere at a distance of 0.75 m and 2.25 m from the labeled tree. The 15N atom% was also determined in the wood, bark, branches and total foliage of the 3 labeled Acacia trees and 9 Eucalyptus trees, 60 days after labeling. Most of the leaves, fine roots and rhizosphere samples of both species were 15N enriched from 5 days after labeling. The δ15N values were higher at a distance of 0.75 m than at 2.25 m in Acacia roots, but were similar at both distances in Eucalyptus roots and the rhizospheres. The wood and bark of Eucalyptus trees sampled at a distance of 6.2 m from the labeled Acacia trees were 15N enriched. This shows belowground N transfer from Acacia to Eucalyptus trees in the field during the first few days after labeling. This facilitation process may provide a significant amount of the nitrogen requirements of trees close to N-fixing trees in mixed forests.
Keywords: 15N; Acacia; Common mycorrhizal network; Eucalyptus; Exudates; Nitrogen facilitation; Nitrogen fixing trees; Stem injection